Measuring the voluntary disclosure of graphical information in annual reports using a new disclosure index - Abdul Rahman, Azhar; Hamdan, Mohd Diah; Ibrahim, Mohd Azhar (Universiti Utara Malaysia, 2006)
The use of graphs in disclosing financial information in corporate annual reports represents a significant dimension of management’s disclosure strategy.This study extends previous research into financial graphs by documenting the nature and extent of graphs use among the 2003 corporate annual reports of the top 50 and bottom 50 listed Malaysian companies ranked by net profit before tax.A disclosure index known as Graphical Information Disclosure Index (GIDI) is developed to measure the level of graphical disclosure.Additionally, the research examines whether companies with ‘good’ and ‘poor’ performance disclose graphs differently; and whether the voluntary disclosure of graphical information can be explained by signalling theory.Drawing on signalling theory, six hypotheses are developed and tested.Sixty-four per cent of companies use graphs; the mean number is 5.3, with plantation companies using the most graphs.The most commonly graphed financial variables are sales, profit, EPS and shareholders’ fund. Evidence is found that graph use is contingent upon favourable performance.Using a wider industry classification, this study also finds a significant difference in the level of disclosure by different industry sectors.Comparison with prior single-country studies reveals that graphs are used less extensively in Malaysia than in the U.S.A., Canada, U.K. and Australia; but more extensively than Hong Kong.The implications of these findings are considered and areas of further research discussed.